2013
DOI: 10.1063/1.4813496
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz-infrared spectra of the rare-earth scandate DyScO3 single crystal

Abstract: Terahertz and infrared spectra of the optical response of DyScO3 single crystal are measured at temperatures from 5 K to 300 K for two different polarizations E‖[1¯01] and E‖[010], i.e., along the two crystallographic directions of the DyScO3 substrates used for growing of thin films and heterostructures. Detailed reference data on the terahertz dielectric characteristics of the DyScO3 substrate are presented. We discuss the mechanisms responsible for electromagnetic absorption. Phonon spectra are analyzed alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
1
1
0
2
Order By: Relevance
“…The substrate spectra show the expected typical phonon characteristics. They are similar to the spectra obtained by other authors [39][40][41] , where further details about them can be found. All 7 modes predicted by the group analysis can be observed along the c-axis while only 14 modes are found in the direction perpendicular to it.…”
Section: B Infrared Spectroscopy Of the Dysco3 Substratesupporting
confidence: 74%
“…The substrate spectra show the expected typical phonon characteristics. They are similar to the spectra obtained by other authors [39][40][41] , where further details about them can be found. All 7 modes predicted by the group analysis can be observed along the c-axis while only 14 modes are found in the direction perpendicular to it.…”
Section: B Infrared Spectroscopy Of the Dysco3 Substratesupporting
confidence: 74%
“…Similar effect was observed also in other scandates. [18][19][20] It is not quite clear what is nature of this effect, because no structural changes in this temperature range are observed. The reflection in this spectral region is very strong and makes difficult to study infrared properties of any film or superlattice deposited on its top in this polarization.…”
Section: A Infrared Spectroscopy Of the Smsco 3 Substratementioning
confidence: 96%
“…Измерения выполнены на инфракрасном фурьеспектрометре "Bruker IFS-113v" (IR FT) и лабораторном импульсном спектрометре терагерцового диапазона с временным разрешением (TDS), описанном в [7]. Методика аналогична использованной в работе [8].…”
Section: физикаunclassified